2013
DOI: 10.7763/ijtef.2013.v4.316
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of Director Remuneration in Malaysia Public Listed Companies

Abstract: Abstract-This study examines the relationships between a family firm, the remuneration committee and director remuneration. The proxies of the remuneration committee are the numbers of committee members. The family firm proxy is a family member, as in the board of directors. The dependent variable (director remuneration) is measured by fees, salary, bonuses and benefit of kin. The sample size of this study is 537 firms listed in Bursa, Malaysia with 1611 panel data from 2007 to 2009. This study finds that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…According to both firm size proxies Ln (Asset) & Ln (Net Sales Revenue), it can be concluded that managing large type companies, either on asset size or sales scale, leads to more managerial remuneration. This finding is consistent with most of the previous studies (Ibrahim et al 2005;Jaafar & James 2013;Yatim 2013).…”
Section: Tests Of Panel Data Regressionssupporting
confidence: 94%
See 2 more Smart Citations
“…According to both firm size proxies Ln (Asset) & Ln (Net Sales Revenue), it can be concluded that managing large type companies, either on asset size or sales scale, leads to more managerial remuneration. This finding is consistent with most of the previous studies (Ibrahim et al 2005;Jaafar & James 2013;Yatim 2013).…”
Section: Tests Of Panel Data Regressionssupporting
confidence: 94%
“…(Coefficient of model 1= -.2161; p <0.01, coefficient of model 2 = -.3088; p <0.1). This finding is in line with results of the study by Jaafar and James (2013) in Malaysian public listed companies. The negative relationship between these two variables is likely due to the agency theory perspective that suggests debt and remuneration as substitute instruments for reducing conflicts between managers and shareholders.…”
Section: Tests Of Panel Data Regressionssupporting
confidence: 92%
See 1 more Smart Citation
“…An effective compensation committee must properly perform its role of controlling director compensation. In the case of family businesses, in search of motivation for long-term success, family members combine power with control to streamline director compensation (Jaafar & James, 2013).…”
Section: Compensation Of Directorsmentioning
confidence: 99%
“…Generally, the remuneration component involves cash such as fees, salaries, and bonuses, and nonfinancial incentives such as stock options or warrants, properties and other in-kinds (Jaafar & James 2013). Salaries, fees and bonuses are the main components of the remuneration package which should meet the expectation and satisfaction of the directors, failing which they may be induced towards personal conflict of interest (Abdul Wahab & Abdul Rahman 2009; Jaafar & James 2013).…”
Section: Director Remunerationmentioning
confidence: 99%